Rigidity dictates spontaneous helix formation of thermoresponsive colloidal chains in poor solvent - Biswas, Bipul; Mitra, Debarshi; KP, Fayis; Bhat, Suresh; Chatterji, Apratim; Kumaraswamy, Guruswamy (ACS Nano, 2021)
The formation of helical motifs typically requires specific directional interactions. Here, we demonstrate that isotropic interparticle attraction can drive self-assembly of colloidal chains into thermo-reversible helices, for chains with a critical level of backbone rigidity. We prepare thermoresponsive colloidal chains by cross-linking PNIPAM microgel-coated polystyrene colloids (“monomers”), aligned in an AC electric field. We control the chain rigidity by varying cross-linking time. Above the LCST of PNIPAM, there is an effective attraction between monomers so that the colloidal chains are in a bad solvent. On heating, the chains decrease in size. For the most rigid chains, the decrease is modest and is not accompanied by a change in shape. Much less rigid chains form relatively compact structures, resulting in a large increase in the local monomer density. Unusually, chains with intermediate rigidity spontaneously assemble into helical structures. The chain helicity increases with temperature and plateaus above the collapse transition temperature of the microgel particles. We simulate a minimal model that captures the spontaneous emergence of the helical conformations of the polymeric chain and provides insight into this shape transition. Our work suggests that a purely mechanical instability for semiflexible filaments can drive helix formation, without the need to invoke directional interactions.